ANALISIS PERMINTAAN RIIL ENERGI LISTRIK DI JAWA TENGAH DAN DI. YOGYAKARTA - Wahyu Hiskia Surbakti; Johanna Maria Kodoatie (Diponegoro Journal of Economics, 2013)
Increased demand for electrical energy that is not accompanied by an increase in electricity production will affect the activities of the community and will ultimately hamper economic growth. This study aims to estimate the demand for electricity in the region of Central Java and DI.Yogyakarta. Dependent variable is the amount of electricity sold (kWh), the independent variable is the number of customers (units) and electricity production cost (U.S. $ / kWh).The data used are secondary data. Data obtained through the documentation of the data owned by PT PLN branch Jatingaleh. The analysis tools used in this research is Multiple linear regression with SPSS 16.00.The results showed that in the household sector (RT) variable influential is the number of consumers. Coefficient of determination equals 74.3% and that’s mean consumers have real effect on electricity demand. The results show that the business sector is the number variable influential consumers. Coefficient of determination equals 22.2% and that’s mean consumers only have little part in the effect on electricity demand. The results show that the industrial sector is the number variable influential consumers. Coefficient of determination equals 65.7% and that’s mean consumers have real effect on electricity demand. The results showed that in the social sector variable influential is the number of consumers. Coefficient of determination equals 65.7% and that’s mean consumers have real effect on electricity demand. The results showed that in the government sector variable influential is the number of consumers. Coefficient of determination equals 72.8% and that’s mean consumers have real effect on electricity demand. And the models of electricity overload demand, the highest demand are almost at the end of year like at September, November and December where means at that’s month the possibility electricity will be off for a while is high.